IMPLEMENTASI METODE EKSPERIMEN SEDERHANA DALAM MENINGKATKAN LITERASI SAINS SISWA PADA PEMBELAJARAN IPAS KELAS V - Ikna Tira Intani; Muhaiminah Jalal; Susy Pransiska (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Objective: This study aims to improve students’ science literacy through the application of simple experimental methods in fifth-grade IPAS learning. The research employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection stages conducted in two cycles. The subjects were 21 fifth-grade students at SDN 073/IX Simpang Sungai Duren. Data were collected through observation, tests, and documentation. The results showed that the application of simple experimental methods improved students’ science literacy, as indicated by the increase in learning mastery from 66.66% in Cycle I to 90.47% in Cycle II. In addition, students’ learning activities improved, as they became more active in observing, experimenting, discussing, and drawing conclusions. Therefore, the simple experimental method is effective in improving students’ science literacy on the topic of the human respiratory system in fifth-grade IPAS learning.